L’usage des automates interactifs dans les lieux publics - Daniel Thierry (Communication)
For the last twenty years, interactive information kiosks have become increasingly present in public places, providing transactional, orientational and informational services plus more didactic functions, particularly in Museology. At a time when their use is being extended to services with a more social character, it raises the question of the limits of their social acceptability. This article reports on two comparative studies, carried out at a twenty-year interval, that describe the progression of the relationship between Man and Machine. It can be observed that a significant "professionalization" of users has taken place, but nothing suggests that this behaviour can be extended beyond this particular group.